LAMP: 3D layered, adaptive-resolution, and multi-perspective panorama—a new scene representation - Zhu, Zhigang; Hanson, Allen R. (Computer vision and image understanding, 2004)
A compact visual representation, called the 3D layered, adaptive-resolution, and multi-perspective panorama (LAMP), is proposed for representing large-scale 3D scenes with large variations of depths and obvious occlusions. Two kinds of 3D LAMP representations are proposed: the relief-like LAMP and the image-based LAMP. Both types of LAMPs concisely represent almost all the information from a long image sequence. Methods to construct LAMP representations from video sequences with dominant translation are provided. The relief-like LAMP is basically a single extended multi-perspective panoramic view image. Each pixel has a pair of texture and depth values, but each pixel may also have multiple pairs of texture-depth values to represent occlusion in layers, in addition to adaptive resolution changing with depth. The image-based LAMP, on the other hand, consists of a set of multi-perspective layers, each of which has a pair of 2D texture and depth maps, but with adaptive time-sampling scales depending on depths of scene points. Several examples of 3D LAMP construction for real image sequences are given. The 3D LAMP is a concise and powerful representation for image-based rendering.